(untitled) (Journal of the College of Basic Education, 2022)
The research aims to prepare an educational curriculum according to the strategies of active discussion and the modified lecture in the collection of the subject of methods of teaching physical education.The researcher used the experimental approach, and the research sample consisted of third-stage students - Department of Physical Education - College of Basic Education - Al-Mustansiriya University, where the research sample consisted of (48) male and female students, who were selected in a simple random way, and they were divided into three groups, the first experimental was studied according to the strategy Active discussion, and the second experimental study according to the modified lecture strategy and the other